A Study of Euphemism in Crime News in Online Media - Risma; M. Nurzin R. Kasau; Suleha; Nuraini Kasman (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study examines the use of euphemism in crime news published on online media platforms, with a particular focus on Detik.com. The purpose of this research is to identify and analyze the forms and functions of euphemism that journalists employ to present sensitive or potentially disturbing information in a more polite, neutral, and socially acceptable manner. The data were collected from crime-related news articles published in February 2025 through a reading and note-taking technique. The analysis involved three stages: data reduction, data display, and conclusion drawing. The findings reveal that euphemism appears in various forms, including abbreviations, loanwords, foreign terms, metaphors, and periphrasis. These linguistic strategies serve multiple functions: softening harsh expressions, concealing sensitive information, maintaining diplomacy, providing educational value, and reducing social anxiety. Overall, the study highlights the role of euphemism in shaping public perception of crime news and its importance in upholding journalistic ethics. The results are expected to contribute to a better understanding of how language use in the media influences communication, objectivity, and sensitivity in news reporting.